Hidden costs of hiding stigma: Ironic interpersonal consequences of concealing a stigmatized identity in social interactions - Newheiser, A.-K. (2015)
People who possess a concealable stigmatized identity (e.g., minority sexual orientation: history of mental illness) often hide this identity from others in order to avoid bias. Despite the possible benefits of this identity management strategy, we propose that instead of increasing acceptance, hiding a stigmatized identity can result in a lowered sense of belonging and even actual social rejection. Across four studies, we show that although individuals living with concealable stigmatized identities report a preference for hiding (vs. revealing) the identity during social interactions, hiding in fact reduces feelings of belonging an effect that is mediated by felt inauthenticity and reduced general self-disclosure (i.e., disclosure of self-relevant information not limited to the stigmatized identity). Furthermore, the detrimental interpersonal effects of hiding (vs. revealing) a stigmatized identity are detected by extemal observers and non-stigmatized interaction partners. Implications for understanding the predicament of people living with stigmatized social identities are discussed.